HMGA1a Induces Alternative Splicing of the Estrogen Receptor-αlpha Gene by Trapping U1 snRNP to an Upstream Pseudo-5′ Splice Site - Ohe, Kenji; Miyajima, Shinsuke; Tanaka, Tomoko; Hamaguchi, Yuriko; Harada, Yoshihiro; Horita, Yuta; Beppu, Yuki; Ito, Fumiaki; Yamasaki, Takafumi; Terai, Hiroki; Mori, Masayoshi; Murata, Yusuke; et al. (Frontiers in Molecular Biosciences, 2018)
Objectives: The high-mobility group A protein 1a (HMGA1a) protein is known as a transcription factor that binds to DNA, but recent studies have shown it exerts novel functions through RNA-binding. We were prompted to decipher the mechanism of HMGA1a-induced alternative splicing of the estrogen receptor alpha (ERα) that we recently reported would alter tamoxifen sensitivity in MCF-7 TAMR1 cells. Methods: Endogenous expression of full length ERα66 and its isoform ERα46 were evaluated in MCF-7 breast cancer cells by transient expression of HMGA1a and an RNA decoy (2’-O-methylated RNA of the HMGA1a RNA-binding site) that binds to HMGA1a. RNA-binding of HMGA1a was checked by RNA-EMSA. In vitro splicing assay was performed to check the direct involvement of HMGA1a in splicing regulation. RNA-EMSA assay in the presence of purified U1 snRNP was performed with psoralen UV crosslinking to check complex formation of HMGA1a-U1 snRNP at the upstream pseudo-5’ splice site of exon 1. Results: HMGA1a induced exon skipping of a shortened exon 1 of ERα in in vitro splicing assays that was blocked by the HMGA1a RNA decoy and sequence-specific RNA-binding was confirmed by RNA-EMSA and ITC measurements. RNA-EMSA combined with psoralen UV crosslinking showed that HMGA1a trapped purified U1 snRNP at the upstream pseudo-5’ splice site. Conclusions: Regulation of ERα alternative splicing by an HMGA1a-trapped U1 snRNP complex at the upstream 5’ splice site of exon 1 offers novel insight on 5’ splice site regulation by U1 snRNP as well as a promising target in breast cancer therapy where alternative splicing of ERα is involved.